MENINGKATKAN MINAT DAN KETERAMPILAN MEMBACA PUISI MENGGUNAKAN MEDIA AUDIO VISUAL PADA SISWA KELAS V SDN 10 ULU MAHUAM - Siregar, Sutan Mara Doli (Jurnal Tematik, 2022)
reading is the most important aspect of learning. One of Indonesian literary works is poetry. Based on the researcher's initial observations, poetry reading skills in fifth grade students are still low. To improve poetry reading skills need the right media. Audiovisual media is an electronic device that can display moving images and audio at the same time in an attractive appearance. This research is an action research as a learning step. The stages of action research are planning, implementation, action, and reflection. The learning improvement actions were carried out in two cycles. The learning outcomes from the improvement of the first cycle were an average of 50% and the second cycle improvement with the increase showed an average of 24.7% with an average value of 78.4%. This shows that audiovisual media can improve learning outcomes in poetry reading skills for class V SDN 10 Ulu Mahuam.